2006
DOI: 10.1681/asn.2005111173
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role for Mast Cells in Omental Tissue Remodeling and Cell Recruitment in Experimental Peritoneal Dialysis

Abstract: Because of its dynamic structure, the omentum plays a key role in the immunity of the peritoneal cavity by orchestrating peritoneal cell recruitment. Because mast cells accumulate in the omentum upon experimental peritoneal dialysis (PD) and may produce angiogenic/profibrotic factors, it was hypothesized that mast cells mediate omental tissue remodeling during PD. Daily treatment with conventional PD fluid (PDF) for 5 wk resulted in a strong omental remodeling response, characterized by an approximately 10-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…Together with previous studies, in which mast-cell-deficient rats also showed significantly reduced angiogenesis in the omentum and in which strong correlations between omental angiogenesis and mast cells have been found, this suggests an important role for mast cells in new blood vessel formation upon PD [41] .…”
Section: Prevention Of Pd-induced Angiogenesissupporting
confidence: 83%
See 1 more Smart Citation
“…Together with previous studies, in which mast-cell-deficient rats also showed significantly reduced angiogenesis in the omentum and in which strong correlations between omental angiogenesis and mast cells have been found, this suggests an important role for mast cells in new blood vessel formation upon PD [41] .…”
Section: Prevention Of Pd-induced Angiogenesissupporting
confidence: 83%
“…The mast cells are found near blood vessels and the number of mast cells in the omentum strongly correlates with the number of blood vessels. PDF exposure in mast cell-depleted wild-type rats and mast cell-deficient Ws/Ws rats shows a significant reduction in omental angiogenesis also indicating a compelling role for mast cells in PD-induced angiogenesis [41] .…”
Section: Peritoneal Cells Involved In Pd-induced Angiogenesismentioning
confidence: 94%
“…IL-4 is a pleiotropic cytokine with major immune regulatory functions, such as in naive T cell differentiation and Th2 polarization (48), alternative macrophage (M2 macrophage) differentiation, and proliferation of tissue-resident macrophages (49), ultimately playing an important role in tissue homeostasis and repair (32,50). Of note, mast cells are essential for the differentiation of macrophages in milky spots of the peritoneal omentum, known to play an important role in pathogen elimination (51). Low amounts of bacteria or endotoxins may diffuse from the gut under steadystate conditions to weakly stimulate PMCs, thereby allowing the proliferation of resident macrophages and maintaining resident cell homeostasis and peritoneal tissue integrity.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the activity of cellular mediators in the peritoneal fluid plays an active role in peritoneal healing. These cellular mediators are produced by the cellular components of the peritoneal fluid such as the mast cells, the macrophages, the neutrophils and the eosinophils [10,11]. Surgical trauma triggers inflammation process which causes an increase in vascular permeability and release of fibrinrich exudates [12].…”
Section: Discussionmentioning
confidence: 99%